Correction of cortriatriatum sinister with classical Raghib's complex using an extracardiac conduit. Issue 11 (4th December 2017) - Ak, Koray; Hamidov, Anar; Ileri, Ciğdem; Tigen, Kursat; Isbir, Selim; Arsan, Sinan
Abstract: We present a 32‐year‐old patient with cortriatriatum sinister with Raghib's complex (a left persistent superior vena cava draining into the left atrium with an absent coronary sinus and an atrial septal defect [ASD]) who underwent successful surgical correction with excision of the cortriatriatum, closure of the ASD, and establishing the drainage of the persistent left superior vena cava to the right atrium via interposition of an extracardiac 13‐mm ringed polytetrafluoroethylene conduit.